Respon Setek Cabang Bambu Kuning (Bambusa Vulgaris) Terhadap Pemberian Aia - Yosepin K. Simangunsong; Indriyanto Indriyanto; Afif Bintoro (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
Yellow bamboo is one of the bamboo species which used for industrial and house-hold materials, because it has a thick trunk outer layer, length of fiber, and beautiful shape. The success of cuttings grown yellow bamboo branch was lack. To increase the success of the yellow bamboo branches grow cuttings used growth regulators. Therefore, the research was conducted by giving indole acetic acid on yellow bamboo branch cuttings. The objective of this research was to known the growth of yellow bamboo branch cuttings by giving indole acetic acid and known the concentration of the indole acetic acid were the best influence on the growth of yellow bamboo branch cuttings. The research was designed with complete randomized design (CRD) with five treatment, five experimental units, and five branch cuttings for each experimental unit. The concentration of indole acetic acid (IAA) was 0 ppm, 100 ppm, 200 ppm,300 ppm, and 400 ppm. To test the homogeneity range done with Bartlett test, the data will be tested by analysis of variance and then further tested with honestly significant difference test. Yellow bamboo branch cuttings growth by percentage of life parameters, number of shoots, shoot length, shoot diameter, and a significant number of leaves is known, whereas for root length parameter is not significant. Keywords: branch cutting, indole acetic acid, yellow bamboo